Application for Marriage Dispensation for Minors Based on Law no. 16 of 2019 concerning Marriage and the Compilation of Islamic Law (Analysis of Religious Court Determination Number 79/Pdt.P/2018/PA.Msb) - Asmadillah, Siti; Songgirin, Amin (Indonesian Scientific Publication, 2023)
Prevention of marriage at a young age becomes difficult to implement with the existence of a marriage dispensation in the Religious Courts. If you see the permissibility of carrying out child marriages, this certainly raises a question mark about the legal certainty given by the judge. The purpose of this research is to find out the legal certainty of an underage marriage dispensation application in accordance with the principles of marriage and KHI and to find out the Islamic view of the Marriage Law on Court Decree No.79/Pdt.P/2018/PA.Msb The research method is descriptive normative. The data was obtain from a literature study. The results of this study are that the legal certainty of judges is not in line with the fundamental of marriage according to the law but in line with the fundamental of marriage according to Islamic law, so in deciding the request for dispensation of marriage the judge is more inclined to the fundamental of Islamic law.